The Imminent of General Surgery: Progressing to Encounter a Fluctuating Practice - Mansoor Aftab, Muhammad Inzamam, Shahid Latif, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: As compared to other countries, the practice of General Surgery in Pakistan has gone through a series of important development over the last 30 years, despite major variable training models. There increasing concern is that the current teaching of General Surgery residency does not hold out enough skills that are essential to practice the scope of General Surgery in Pakistan. Procedure: Executed by a National Force on the General Surgery Future, this project directed to advance guidance on the favorable configuration of Training on General Surgery in Multan. A consecutive series of studies based on evidence and a survey was introduced to inform these guidelines. Results: The general results of a procedure in any study show the complexity of the practice in General Surgery. 1 Location matters a lot for a surgeon to practice surgery 2 General surgery accompanies a strong grip for the overall clinical competence as well 3 Today general surgeons experience a subspecialized training too 4 Writing a proper report and guidelines for proper future surgical goals is also a part of training for General surgeons today To be a general surgeon in the 21st century, these are the four recommendations that are necessary to maintain. Conclusion: This project mainly refers to the importance of location for fresh general surgery graduates, emphasizing the impact of variable location in contrast with the implementation of the same objectives of the surgery. The results of this study were sent to the Nishtar College to review the requirements of training and the work on a more precise and comfortable working scheme. Hence, we ensured that the GSRTP General Surgery Residency and Training Programs could work for the wider range of practice all around Pakistan for better training practices.